A cross-sectional study to evaluate the association of hyperbilirubinaemia on markers of cardiovascular disease, neurocognitive function, bone mineral density and renal markers in HIV-1 infected subjects on protease inhibitors. Issue 3 (3rd May 2016) - Barber, T. J.; Moyle, G.; Hill, A.; Jagjit Singh, G.; Scourfield, A.; Yapa, H. M.; Waters, L.; Asboe, D.; Boffito, M.; Nelson, M.
Abstract : Background: Ongoing inflammation in controlled HIV infection contributes to non-AIDS comorbidities. High bilirubin appears to exhibit an anti-inflammatory effect in vivo . We therefore examined whether increased bilirubin in persons with HIV was associated with differences in markers of inflammation and cardiovascular, bone, renal disease, and neurocognitive (NC) impairment. Methods: This cross-sectional study examined inflammatory markers in individuals with stable HIV infection treated with two nucleoside reverse transcriptase inhibitors and a boosted protease inhibitor. Individuals recruited were those with a normal bilirubin (NBR; 0–17 μmol/L) or high bilirubin (>2.5 × upper limit of normal). Demographic and anthropological data were recorded. Blood and urine samples were taken for analyses. Pulse wave velocity (PWV) measurement, carotid intimal thickness (CIT), and calcaneal stiffness (CSI) were measured. Males were asked to answer a questionnaire about sexual function; NC testing was performed using CogState. Results: 101 patients were screened, 78 enrolled (43 NBR and 35 HBR). Atazanavir use was significantly higher in HBR. Whilst a trend for lower CIT was seen in those with HBR, no significant differences were seen in PWV, bone markers, calculated cardiovascular risk (Framingham), or erectile dysfunction score. VCAM-1 levels were significantly lower in the HBR group. HBR was associated with lower LDL and triglyceride levels. NBR was associated with a calculated FRAX significantly lower than HBR although no associations were found after adjusting for tenofovir use. No difference in renal markers was observed. Component tests of NC testing revealed differences favouring HBR but overall composite scores were similar. Discussion : High bilirubin in the context of boosted PI therapy was found not to be associated with differences in with the markers examined in this study. Some trends were noted and, on the basis of these, a larger, clinical end point study is warranted.